Energy, exergy, and environmental (3E) assessments of an integrated molten carbonate fuel cell (MCFC), Stirling engine and organic Rankine cycle (ORC) cogeneration system fed by a biomass-fueled gasifier. (29th November 2019) - Salehi, Akbar; Mousavi, Seyed Mostafa; Fasihfar, Ahmad; Ravanbakhsh, Mehdi
Abstract: In this paper, a novel syngas-fed combined cogeneration plant, integrating a biomass gasifier, a molten carbonate fuel cell (MCFC), a heat recovery steam generator (HRSG) unit, a Stirling engine, and an organic Rankine cycle (ORC), is introduced and thermodynamically analyzed to recognize its potentials compared to the previous solo/combined systems. For the proposed system, energetic, exergetic as well as environmental evaluations are performed. Based on the results, the gasifier and the fuel cell have a significant contribution to the exergy destruction of the system. Through a parametric study, the current density and the stack temperature difference are known as the main effective factors on the plant performance. Meanwhile, dividing the whole system into three sub-models, i.e., model (1): power production plant including the gasifier and MCFC without including Stirling engine, HRSG, and ORC unit, model (2): the cogeneration system without ORC unit, and model (3): the whole cogeneration system, an environmental impact assessment is carried out regarding CO2 emission. Considering paper as biomass revealed that maximum value of exergy efficiency is 50.18% with CO2 emissions of 28.9 × 10 −2 t.MWh −1 which compared to the solo MCFC system indicates 28.40% increase and 13.3 × 10 −2 t.MWh −1 decrease in exergy efficiency and CO2 emission, respectively. Graphical abstract: Image 1 Highlights: The 3E analyses of a CHP plant based on biomass gasifier and MCFC are performed. The waste heat of the biomass-fueled MCFC system is recovered by HRSG, Stirling engine, and ORC. The system yields an exergy efficiency of 50.18% with a CO2 emission of 0.289 t/MWh. The gasifier and fuel cell have the highest rates of exergy destruction.